HUKUM ROMAWI DAN HUKUM GERMAN PADA BAGIAN AWAL ABAD PERTENGAHAN ANTARA LAIN DI DALAM NEGARA FRANKA - Joko Suprianto; M. Nur Rahmadani; Revan Meirisco; Muhammad Sunaryo (STKIP Subang, 2024)
In the early Middle Ages, after the fall of the Western Roman Empire, there was a blending of two major legal systems that influenced the development of law in Europe: Roman Law and Germanic Law. Although these two legal systems were fundamentally different, they interacted and adapted under the influence of the barbarian kingdoms, particularly within the Frankish Kingdom. This article examines the comparison between Roman Law, based on written principles, and Germanic Law, which was more customary and oral, and how both were applied and synthesized under the rule of Charlemagne. By analyzing the influence and implementation of these two legal systems, this study shows that while Roman Law was more structured and systematic, Germanic Law played an important role in maintaining social balance through community-based dispute resolution mechanisms. Through Charlemagne’s efforts to codify laws in the Capitularies, which incorporated elements from both legal systems, a legal synthesis was created that influenced the formation of modern legal systems in Europe, including the civil law tradition. This research aims to provide insight into how these two different legal traditions interacted and contributed to the development of a more organized legal structure in the Frankish Kingdom, as well as their long-term impact on European law.